Pretreatments Applied to Wheat Straw to Obtain Bioethanol - Carmen Otilia Rusănescu; Maria Ciobanu; Marin Rusănescu; Raluca Lucia Dinculoiu (Applied Sciences, 2024)
This work is a comprehensive study focusing on various methods for processing wheat straw to enhance its suitability for bioethanol production. It delves into mechanical, physical, chemical, and biological pretreatments, each aimed at improving the enzymatic hydrolysis and fermentation processes necessary for bioethanol production. Mechanical and physical pretreatments involve reducing the size of wheat straw to improve enzymatic hydrolysis. Physical methods include heating and irradiation, which alter the structural properties of wheat straw. Chemical pretreatments involve using acids, alkalis, and organic solvents to remove lignin and hemicellulose, making cellulose more accessible for hydrolysis. Biological pretreatments utilize microorganisms and fungi to degrade lignin and other complex compounds, enhancing the breakdown of cellulose. The study presents data on the effectiveness of these treatments in terms of lignin removal, sugar yield, and overall bioethanol production efficiency. The research is aligned with the global move towards renewable energy sources and emphasizes the importance of utilizing agricultural waste, like wheat straw, for sustainable energy production.